2015
DOI: 10.4103/0028-3886.158191
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral venous thrombosis: An Indian perspective

Abstract: Cerebral venous thrombosis (CVT) is an uncommon cause of stroke with extremely varied clinical presentations, predisposing factors, imaging findings, and outcomes, and thus can be extremely challenging to diagnose. Accurate and prompt diagnosis of CVT is crucial because timely and appropriate therapy can reverse the disease process and significantly reduce the risk of acute complications and long-term squel. In this article, we have reviewed the epidemiology, causative factors, clinical features, diagnosis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Presently, anticoagulation with hydration is the first-line treatment for CVST. Anticoagulation prevents propagation of the thrombus, hastens its spontaneous resolution, and aids in the prevention of deep vein thrombosis and embolism, without adversely promoting intracranial hemorrhage (ICH) (2, 19, 25, 38). ICH is not considered a contraindication for anticoagulation (9).…”
Section: Anticoagulation In Cvstmentioning
confidence: 99%
“…Presently, anticoagulation with hydration is the first-line treatment for CVST. Anticoagulation prevents propagation of the thrombus, hastens its spontaneous resolution, and aids in the prevention of deep vein thrombosis and embolism, without adversely promoting intracranial hemorrhage (ICH) (2, 19, 25, 38). ICH is not considered a contraindication for anticoagulation (9).…”
Section: Anticoagulation In Cvstmentioning
confidence: 99%
“…Anticoagulation is currently the first-line treatment for CVST, and systemic anticoagulation is effective in preventing falling of the thrombus and deep vein thrombosis and embolism. 11 The 2017 European Stroke Organization guidelines for the diagnosis and treatment of CVST, endorsed by the European Academy of Neurology, recommend the following for anticoagulation therapy in patients with CVST: 12 A therapeutic dosage of heparin for all patients with acute CVST, even in the presence of intracerebral hemorrhage. Low-molecular-weight heparin over unfractionated heparin except in patients who are allergic to low-molecular-weight heparin or if rapid anticoagulant effect reversal is required.…”
Section: Discussionmentioning
confidence: 99%
“…24 Most (89.2%) observed that CVT was more common amongst young adults (< 45 years). 25 Common etiologies of CVT were: pregnancy/postpartum (42.8%), hyperhomocystienemia (31.7%), OCP usage (20%), and polycythemia (5.5%). Many (68.2%) used DOAC in treatment of CVT.…”
Section: Cerebral Venous Sinus Thrombosismentioning
confidence: 99%